Game-Based Learning Media Training for Early Childhood for 21st-Century Teachers - Ferry Darmawan; Hakim, Arif; Novita, Sophia (UPT Publikasi Ilmiah UNISBA, 2024)
Abstract. To be able to carry out learning in the digital era, teachers must be literate in technology and information. We are currently in the era of the Industrial Revolution 4.0, which demands harmony between humans and information technology in finding solutions to various problems and creating creative and innovative opportunities. One of the competencies of 21st-century teachers is to develop interactive learning media based on digital technology. However, the reality in the field is that there are limited facilities and infrastructure, so there needs to be another motivation to develop ICT in the learning process of early childhood education (PAUD). This activity uses the Participatory Action Research (PAR) method, which is a transformative approach that aims to solve problems and fulfill the orientation on empowerment and practical needs of community change. The training participants are representatives of PAUD teachers in the Astanaanyar sub-district, under the coordination of the POKJA Bunda PAUD Astana Anyar sub-district. The result of this training is the increased ability of teachers to develop learning media in the form of games using the PowerPoint program, commonly known as a presentation application.